Hostile takeovers and the correction of managerial failure - Franks, Julian; Mayer, Colin (Journal of Financial Economics, 1996)
This paper examines the disciplining function of hostile takeovers in the U.K. in 1985 and 1986. We report evidence of high board turnover and significant levels of post-takeover restructuring. Large gains are anticipated in hostile bids as reflected in high bid premiums. However, there is little evidence of poor performance prior to bids, suggesting that the high board turnover does not derive from past managerial failure. Hostile takeovers do not therefore perform a disciplining function. Instead, rejection of bids appears to derive from opposition to post-takeover redeployment of assets and renegotiation over the terms of bids.